2018
DOI: 10.1016/j.omtn.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

circHLA-C Plays an Important Role in Lupus Nephritis by Sponging miR-150

Abstract: Circular RNAs (circRNAs) participate in the pathogenesis of various diseases by sponging microRNAs (miRs). However, the roles of circRNAs remain unreported in glomerular diseases. We previously reported that miR-150 positively correlated with renal chronicity index in patients with lupus nephritis (LN). We aimed to investigate renal circRNA profiling and the interaction between circRNAs and miR-150 in LN patients. Six renal biopsies from untreated female patients with LN class IV and five normal kidney tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 41 publications
5
71
0
Order By: Relevance
“…The relationship between serum creatinine and hypertension has been released . Luan et al also found that circRNAs have a positive correlation with serum creatinine and act as a sponge for hsa‐miR‐150 . Our results have shown the same tendency in hsa_circ_0037909 expression levels and serum creatinine concentration.…”
Section: Discussionsupporting
confidence: 80%
“…The relationship between serum creatinine and hypertension has been released . Luan et al also found that circRNAs have a positive correlation with serum creatinine and act as a sponge for hsa‐miR‐150 . Our results have shown the same tendency in hsa_circ_0037909 expression levels and serum creatinine concentration.…”
Section: Discussionsupporting
confidence: 80%
“… 7 Functionally, recent studies have shown that circRNAs are enriched at the miRNA-binding sites and play the role of miRNA sponges in cells, thus releasing the inhibitory effect of miRNAs on their target genes and increasing the target gene expression, which is known as the competitive endogenous RNA (ceRNA) mechanism. 16 , 17 In addition, circRNAs play an important regulatory role in cancer via their interaction with cancer-associated miRNAs. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Libraries were controlled for quality and quantified using the BioAnalyzer 2100 system (Agilent Technologies, Inc). The RNA libraries were denatured as single‐stranded DNA molecules, captured on flow cells (Illumina), and amplified in situ as clusters and finally sequenced for 150 cycles on HiSeq 4000 Sequencer (Illumina) as described …”
Section: Methodsmentioning
confidence: 99%